Inspection of the Scene During the Investigation of a Terrorist Act with the Use of Biological Weapons (Bio – Terrorism) - BAINAZAROVA, Gulbanu Zhumaniyazovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
In the article, we discuss the features of one of the investigative actions, governed by the Criminal Procedure Code of the Republic of Kazakhstan – the inspection of the scene during the investigation of a terrorist act, a crime described in Art. 255 of the Criminal Code of the Republic of Kazakhstan, committed with the use of biological weapons. Although at the moment there is no previous history of the terrorist use of biological weapons in the Republic of Kazakhstan (RK), in the context of activation of Islamic extremism crime investigation authorities should be prepared for any of its manifestations, so the research conducted within the framework of the present article is extremely timely and relevant. The author discusses the investigative actions, in particular the inspection of the scene, the features of which are quite significant in case of investigation of an act of bio-terrorism. The consideration of these features can ensure a successful investigation of the act of bio-terrorism, and on the contrary, ignoring them may not only complicate the investigation, but also endanger the lives and health of participants in the investigation.